2022
DOI: 10.1007/s00158-022-03376-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-material design optimization of optical properties of particulate products by discrete dipole approximation and sequential global programming

Abstract: The optimal design of nanoparticles with respect to their optical properties is one of the main foci within nanoparticle technology. In this contribution, we suggest a new design optimization method in the framework of which the discrete dipole approximation (DDA) is used to approximate the solution of Maxwell’s equation in time-harmonic form. In the core of the optimization method, each dipole is repeatedly assigned a material property from a given material catalog until a local minimum for the chosen design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…For particles of these sizes, it has been reported that a quantum mechanical description agrees with classical approaches [27,34]. Comparable computational methods like Finite Element Method (FEM) and Finite Difference Time Domain (FDTD) do not scale well in time and accuracy for differently sized systems [35][36][37]. A comparison of our DDA results with the multilayer Mie theory by Yang et al [32] can be found in Figure 1, and the DDA and Mie calculations align almost perfectly.…”
Section: Methodsmentioning
confidence: 51%
“…For particles of these sizes, it has been reported that a quantum mechanical description agrees with classical approaches [27,34]. Comparable computational methods like Finite Element Method (FEM) and Finite Difference Time Domain (FDTD) do not scale well in time and accuracy for differently sized systems [35][36][37]. A comparison of our DDA results with the multilayer Mie theory by Yang et al [32] can be found in Figure 1, and the DDA and Mie calculations align almost perfectly.…”
Section: Methodsmentioning
confidence: 51%
“…43 Dropping this assumption and considering anisotropic particles or even distributions thereof, impedes a full analysis of the admissible color range, but still allows for optimization of particle structure with respect to color. 44,45 However, such settings require specialized optimization techniques. 46 Moving forward, our approach involves working with experimentally produced NP suspensions with variations in size and chemical composition.…”
Section: Theoretically Available Color Spacementioning
confidence: 99%
“…the discrete dipole approximation (DDA). The optimization of particle designs in DDA has been considered in [17] for a small number of incoming wavelengths. However, as such methods have vastly higher computational cost and our settings require optimization with respect to infinitely many wavelengths, we focus on Mie particles in this contribution, to allow for a more detailed analysis of the optimization problems.…”
Section: The Cielab Color Space and Mie Theorymentioning
confidence: 99%